2010
DOI: 10.1080/1406099x.2010.10840478
|View full text |Cite
|
Sign up to set email alerts
|

Comparing tertiary graduates with and without student loans in Latvia

Abstract: Using a nationally representative sample, this paper describes the profile of student borrowing in Latvia. The paper, more specifically, explores whether higher education graduates with student loans are significantly different from graduates without student loans in Latvia. We compare two groups of university graduates in terms of their demographic and household characteristics, income, and activity in the labor market in terms of the rank of appointment in the company and supplementary income job. Using data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…An ethnicity variable in relation to student borrowing in Latvia was examined by Ait Si Mhamed and Kaša (2010). They found that student loans are mostly held by ethnic Latvians compared to other ethnic groups in the country (Ait Si Mhamed & Kaša, 2010). Thus, the ethnicity variable is not included in the analysis in the current paper.…”
Section: Profiles Of Graduates With Student Debtmentioning
confidence: 98%
See 2 more Smart Citations
“…An ethnicity variable in relation to student borrowing in Latvia was examined by Ait Si Mhamed and Kaša (2010). They found that student loans are mostly held by ethnic Latvians compared to other ethnic groups in the country (Ait Si Mhamed & Kaša, 2010). Thus, the ethnicity variable is not included in the analysis in the current paper.…”
Section: Profiles Of Graduates With Student Debtmentioning
confidence: 98%
“…This analysis is relevant as it will inform which groups of graduates are likely to hold higher student debt levels. The ethnicity variable will not be considered in our analysis because earlier research on higher education graduates with student debt in Latvia has shown that only an insignificant number of non-Latvians hold student debt (Ait Si Mhamed & Kaša, 2010).…”
Section: Variables For Analysismentioning
confidence: 99%
See 1 more Smart Citation